Application of Quizzz to Pascal Law Material in Increasing Student Response - Zainul Arifin; Mohamada Zaky Tatsar (SAGA: Journal of Technology and Information System, 2023)
Abstract. The research is motivated by the rapid development of the times so that there is a need for the latest innovations for students so as not to be left behind, especially in the field of technology, the method used in this research uses a quantitative method. The population and sample in this study were class XI MIPA with 19 students at MA Darul Ulum Karangpandan. The results of the analysis of student responses to the application of Quizizz were that students were interested and happy to learn to use Quizizz. This is evidenced by the results of the questionnaire data, namely the answers to the results of class XI MIPA with 19 students having an average of 78% strongly agree, 100% agree, 12% doubt, 0% disagree, and 0% strongly disagree. Based on the results of the study, it can be concluded that there is an effect of Quizizz on increasing student responses to Pascal's legal material.